The Impact of the Implementation of the Independent Curriculum, Use of Technology, Organizational Structure Changes, Competency Development, and Motivation on Organizational Culture Change among Early Childhood Teachers in Lahat District - Ilian, Neni; Samsuddin , Harun; Darmin, Darmin (Universitas Dehasen Bengkulu, 2025)
Educational reform in Indonesia, particularly through the implementation of the Merdeka Curriculum, requires Early Childhood Education (PAUD) teachers to adapt in various aspects, including technology adoption, organizational restructuring, competence development, and work motivation. This study aims to analyze the influence of Merdeka Curriculum implementation, technological utilization, organizational structure changes, teacher competence development, and motivation on the organizational culture transformation among PAUD teachers in Lahat District. A quantitative approach was applied, using surveys, interviews, and documentation as data collection methods. The results indicate that all five variables, both partially and simultaneously, have a significant impact on shaping an adaptive, collaborative, and professional organizational culture. However, challenges such as limited training access, lack of technological infrastructure, and resistance to change remain, requiring more effective change management strategies. The findings are expected to contribute to policy formulation and educator development programs aligned with the core principles of the Merdeka Curriculum.